DIGITAL INFORMATION SOURCES ABOUT SEMIOTIC ELEMENTS OF FAMOUS PRODUCT BRANDS - Mile Čolić; Ivan Dunđer; Ernest Vlačić (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
Today, various products are presented on the internet in the form of pictorial and symbolic content that represents certain information, and thus digital sources of product information are gaining in importance. The internet as a new medium has a strong influence on the promotion of each product brand and is widely used for corporate marketing activities. Semiotics as a science deals with the study of signs, and observed from the perspective of information theory, it studies the meaning of signs in the process of information transfer. Each product brand, assuming that it has the necessary quality and properties, achieves its market success through effective communication with the end user. In other words, in order for a product to succeed and survive on the market today, it is necessary for it to become an acceptable and desirable sign for a wider group of consumers. For this reason, each product is defined by a product brand, and the basic elements of a product brand are the brand name, brand mark or logo, slogan, and trademark. The aim of this paper is to point out the market dependence of products on quality advertising and labeling, and on the example of successful foreign and domestic products to explore the meaning of recognizable promotion that is determined by quality labeling. The fundamental research question in this paper is to what extent carefully designed slogans determine the recognizability of semiotic elements of product brands on the internet. In the paper, a qualitative and quantitative analysis of semiotic elements of brands of foreign and Croatian products on the internet is performed, and the values for the brand name, logo, and slogan are determined.